Vitamins and Human Health: 3rd Edition Editorial - Mackenzie Guettler; Tyler Barker (Nutrients, 2026)
Vitamins are essential micronutrients that regulate numerous physiological responses critical to human health: cellular metabolism, immune function, endocrine signaling, tissue repair, musculoskeletal performance, and more [...]